2016
DOI: 10.1080/08949468.2016.1131494
|View full text |Cite|
|
Sign up to set email alerts
|

Seeing Cellular Debris, Remembering a Soviet Method

Abstract: A 1962 photomicrograph of a mosquito taken in what was then a Tanganyikan mountain laboratory offers a prompt to consider the social salience and affective power of scientific images. Drawing inspiration from anthropological work on photographic practices, this article excavates the diverse geopolitical and domestic contexts of the image's production, consumption and circulation, so as to grasp the relationship between scientific labors and lives. As much souvenir as "epistemic thing," the photomicrograph prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Perhaps this was why the Tanzanian science workers took distinct pride in technical routine skills and the virtues of fieldwork (see also Poleykett and Mangesho 2016). Yet, the satisfaction derived from technical prowess and thorough fieldwork was also found in their European colleagues’ narratives: in Wilkes’ lifelong mastery of mosquito dissection, which he continued teaching at the London School half a century later (see Kelly 2016), in Raybould's meticulous in vitro recreation of blackflies’ complex breeding conditions, and in the much-extolled pleasures of field data collection.…”
Section: Good Science and Political Doubtsmentioning
confidence: 98%
“…Perhaps this was why the Tanzanian science workers took distinct pride in technical routine skills and the virtues of fieldwork (see also Poleykett and Mangesho 2016). Yet, the satisfaction derived from technical prowess and thorough fieldwork was also found in their European colleagues’ narratives: in Wilkes’ lifelong mastery of mosquito dissection, which he continued teaching at the London School half a century later (see Kelly 2016), in Raybould's meticulous in vitro recreation of blackflies’ complex breeding conditions, and in the much-extolled pleasures of field data collection.…”
Section: Good Science and Political Doubtsmentioning
confidence: 98%
“…Our open‐ended fieldwork in the remains of the decaying station brought together a network not just of elderly people around Amani and, in fact, the globe, but also of things: maps and (unbuilt) architectural plans, stored experimental devices and chemicals, Super‐8 reels of daily life and work, a buried laboratory bottle in an abandoned roadside bar, sentimental English novels in the guesthouse, Wilhelminian 4 furniture in village homes, tree‐high feral tea plants in the former botanical gardens, rows of geraniums bordering overgrown lawns around collapsing bungalows – and surprising connections between them, extending from Amani into European homes and attics, museum collections and laboratories (see, e.g., Kelly 2016).…”
Section: Collectionmentioning
confidence: 99%
“…Histories of medical technology development in socialist contexts, such as the Czechoslovak innovation of the contact lens (Nisonen-Trnka, 2010) or Tanganyikan malaria research based on the "Soviet method" of mosquito dissection (Kelly, 2016), have revealed a history of medicine rich in innovation, lasting scientific exchange and political experiments in healthcare. A prominent example of this is bacteriophage therapy research, abandoned in the West with the appearance of antibiotics, but continuing in Georgia and Poland (Myelnikov, 2018).…”
Section: Global Socialist Connectionsmentioning
confidence: 99%